Novel approach to theoretical investigation of heavy quasi-molecules - Artemyev, Anton; Surzhykov, Andrey; Stöhlker, Thomas (Journal of physics. Conference Series, 2012)
The new approach to the theoretical investigation of heavy quasi-molecules is created. The approach is based on the application of finite basis set method in Cassini coordinates. The method allows the generation of accurate quasi-complete spectrum of two-center Dirac Hamiltonian eigen-states.